Assentamentos habitacionais populares e o desenvolvimento sustentável : a realidade do bairro 17 de março, Aracaju - Sergipe - Santos, Danielle Menezes dos (2014)
Urban planning enables the quality of life of the population. The execution of a neighborhood when planned, allows sustainable community development. In view of this the present study aims to assess the implementation of sustainable development indicators for public housing settlements in Aracaju - SE, in order to promote sustainable development, case of 17 March Quarter. To meet the main objective had to be defined specific objectives: to assess the situation of the Neighborhood March 17 according to residents, to assess the sustainable development indicators IBGE that fall to the Neighborhood 17 March and indicate actions that provide improvements to public housing settlements. In order to respond to the issues raised, the defined implementation methodology was exploratory and descriptive research with the lifting of quantitative and qualitative data. The technical procedures were used: documentary and bibliographic research and questionnaires with residents of the settlement and employees of the Municipal Aracaju. The research was the first and second stage of the neighborhood delivered through June 2013, totaling 1,490 properties, of which 251 households were surveyed. The analysis and discussion of the data were performed after the same are tabulated and graphed later founded and analyzed for Sustainable Development Indicators IBGE. The characteristics of the building, common area, services, infrastructure, mobility, economic, social and health were evaluated and the results found show that, the urban planning, the neighborhood has no quality of life and some of the requirements were not met. Regarding indicators, the district does not have satisfactory situation, which demonstrates the need for action by City Hall for residents to have quality of life and sustainable development in the neighborhood occurs.